Improving Characteristics of Diesel Engine by Changing the Engine's Charging and Design Method - Le, Viet Hung; Do, Van Dung; Nguyen, Anh Thi; Luong, Huynh Giang; Vo, Van An; Do, Minh Dung (Old Journal, 2019)
This paper represents research on improving the working characteristics of a direct injection 16.5 Hp diesel engine by changing the engine’s charging and design method. With the help of SolidWorks 3D software, previous design and rendering plans were compared and evaluated visually compared to the new method. The criteria which are surveyed and evaluated are design time, flatness and smoothness of the object’s surface. The intake manifold of the engine is designed and modeled using a newly developed method, which is evaluated by experiments in comparison with the old method. Operation improvement of the engine’s specifications such as max power, specific fuel consumption at continuous rated power is the goal of this study.